PENGARUH MALTOSA SEBAGAI KRIOPROTEKTAN EKSTRASELULER DALAM MENINGKATKAN KUALITAS SEMEN BEKU GUNA MENDUKUNG KEBERHASILAN TEKNOLOGI INSEMINASI BUATAN - herdis, herdis; darmawan, i wayan angga (Badan Pengkajian dan Penerapan Teknologi, 2012)
The research carried out to observe the effect of maltose addition on the quality of frozen semen of garut rams. Semen was collected once a week using artificial vagina from six mature garut rams. Semen was equilibrated at 5oC for four hours, frozen and stored in liquid nitrogen. The thawing was carried out at the temperature 30oC for 30 seconds. The result showed that percentages of viable sperm for addition of maltose 1,2 g / 100 ml extender (68,50 ± 0,84%) was significantly difference (P<0,05) than control (54,83 ± 1,94%) and addition of maltose 0,6 g / 100 ml extender (65,67 ± 1,03 %). The percentages of progressive motile sperm and percentages of plasma membrane for addition of maltose 1,2 g / 100 ml extender (53% and 64,67%) were significantly difference (P<0,05) than control (43% and 53,83%) but were not significantly different (P>0,05) from addition of maltose 0,6 g / 100 ml extender (50,83% and 64,67%)respectively. In conclusion, the addition of maltose 1,2 g / 100 ml extender is optimal dose to improve the quality of frozen semen of garut rams.